Historical pesticide applications coincided with an altered diet of aerially foraging insectivorous chimney swifts - Nocera, Joseph J. (The Royal Society, 2012)
Numerous environmental pressures have precipitated long-term population reductions of many insect species. Population declines in aerially foraging insectivorous birds have also been detected, but the cause remains unknown partly because of a dearth of long-term monitoring data on avian diets. Chimney swifts (Chaetura pelagica) are a model aerial insectivore to fill such information gaps because their roosting behaviour makes them easy to sample in large numbers over long time periods. We report a 48-year-long (1944–1992) dietary record for the chimney swift, determined from a well-preserved deposit of guano and egested insect remains in Ontario (Canada). This unique archive of palaeo-environmental data reflecting past chimney swift diets revealed a steep rise in dichlorodiphenyltrichloroethane (DDT) and metabolites, which were correlated with a decrease in Coleoptera remains and an increase in Hemiptera remains, indicating a significant change in chimney swift prey. We argue that DDT applications decimated Coleoptera populations and dramatically altered insect community structure by the 1960s, triggering nutritional consequences for swifts and other aerial insectivores.